Cloning and Characterization of a Curcin Gene Encoding a Ribosome Inactivating Protein from Jatropha curcas - Lin, J.; Li, Y.X.; Zhou, X.W.; Tang, K.X.; Chen, F.
A curcin gene was isolated by using genomic walker technology and revealed to encode the type-1 ribosome inactivating proteins (RIPs). Analysis of 1802 bp segments revealed the gene including a 694 bp 50 flanking region, a 882 bp open read frame (ORF)and a 226 bp 30 flanking region. There are one putative TATA boxes and two possible CAAT box lie in the 50-flanking region. The ORF encodes a 32 kDa precursor, which contains a 42 amino acid signal peptide. Two possible polyadenylation signals are found in the 30-flanking region. No introns were found, which is typical of other RIPs gene that has been sequenced. The deduced amino acid sequence of Curcin gene coding region shares high homology with RIPs, e.g. ricin A-chain, gelonin, abrin A-chain, bryodin, trichosanthin and momorcharin, which were found to be 34
Keywords: JATROPHA CURCAS; CURCIN; GENOMIC CLONING; GENOMIC WALKER TECHNOLOGY; RIBOSOME INACTIVATING PROTEIN